2019
DOI: 10.31234/osf.io/pk82n
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Attitudes towards Open Science and Public Data Sharing: A Survey among Members of the German Psychological Society.

Abstract: Central values of science are, among others, transparency, verifiability, replicability and openness. The currently very prominent Open Science (OS) movement supports these values. Among its most important principles are open methodology (comprehensive and useful documentation of methods and materials used), open access to published research output, and open data (making collected data available for re-analyses). We here present a survey conducted among members of the German Psychological Society (N = 337), in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 4 publications
0
30
0
Order By: Relevance
“…In recent survey in the United Kingdom with 1724 participants 21% of them have had experience depositing primary data in online repositories although they have very positive opinion about data sharing (13). In a recent survey among members of the German psychological society (N=303) Abele-Brehm et al construct a scale measuring hopes (10 items, Cronbach α=0.90) and fears (4 items, Cronbach α=0.67) towards data sharing, and the positive attitude – “hopes” were neutral (around 3.0), but their experience with data sharing was not measured (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent survey in the United Kingdom with 1724 participants 21% of them have had experience depositing primary data in online repositories although they have very positive opinion about data sharing (13). In a recent survey among members of the German psychological society (N=303) Abele-Brehm et al construct a scale measuring hopes (10 items, Cronbach α=0.90) and fears (4 items, Cronbach α=0.67) towards data sharing, and the positive attitude – “hopes” were neutral (around 3.0), but their experience with data sharing was not measured (21).…”
Section: Discussionmentioning
confidence: 99%
“…Although one-question measuring is a useful method for “snapshot measuring” (20), measuring attitudes with only a single question is generally not considered an optimal approach. To the best of our knowledge, no studies, except the Brehm et al study (21) and Curty et al (22), used a scale (and reported on its reliability and validity) to measure attitudes toward any aspect of open science. It was, therefore, our goal to construct and validate such a scale and use it to explore attitudes of Croatian scientists towards it.…”
Section: Introductionmentioning
confidence: 99%
“…Open data practices also remain controversial among academics due to perceived individual costs in today's hypercompetitive research environment [22][23][24][25][26] . Many researchers feel a sense of ownership over their data and fear that potential individual benefits do not make up for future publications lost by relinquishing priority of access to the data they collectedthe fear of being 'scooped' 4,6,13,27 .…”
mentioning
confidence: 99%
“…Research to date has centered on understanding the opinions of researchers in order to identify 'motivations and enablers' or 'fears and barriers' to data sharing 5,10,18,26,[31][32][33][34] . A recent systematic review of researcher's attitudes towards open data identified five factors that strongly influence data sharing: seniority, age, lack of time, loss of control over one's data, and data misappropriation 18 .…”
mentioning
confidence: 99%
See 1 more Smart Citation